2015
DOI: 10.1002/nau.22949
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on the effects of regular and decaffeinated coffee on urinary symptoms in young and healthy volunteers

Abstract: The study suggests that avoiding high-dosage coffee consumption prevents urgency and frequency, which supports recommendations to limit caffeinated beverages. The study differentiates between subjects having a history of low and frequent coffee use. Subjects, who are not used to regular coffee consumption, seem to be more vulnerable to the effects of coffee on urinary symptoms. Better understanding of the effects of coffee on urinary symptoms may improve patients counseling. Neurourol. Neurourol. Urodynam. 36:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Therefore, caffeine intake is considered to be associated with lower risk of kidney stones . A previous prospective study on the effects of caffeine in coffee suggested that coffee reduction can be a strategy in preventing urinary symptoms, such as frequency, urgency, and bladder pain syndrome …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, caffeine intake is considered to be associated with lower risk of kidney stones . A previous prospective study on the effects of caffeine in coffee suggested that coffee reduction can be a strategy in preventing urinary symptoms, such as frequency, urgency, and bladder pain syndrome …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, caffeinated drinks have become a staple of the average diet; more than 85% of adults in the United States regularly consume caffeine . A longitudinal study of caffeine intake in young healthy volunteers found that subjects who regularly drank coffee had significant increases in urinary urgency and frequency . Additionally, a separate study observed that greater coffee intake raised the odds of LUTS progression in men and women more than carbonated or citrus beverages .…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that more than 59% of adults in the United States drink coffee beverages and similarly in other developed countries [ 1 ]. While consumption of coffee is prevalent, approximately 15% of the U.S. population has stopped drinking coffee altogether, citing concerns about health, coffee reduction has been a strategy to prevent urinary tract symptoms such as bladder pain syndrome [ 1 ]. There are reports of randomized controlled trials on chronic consumption of coffee that confirmed a small but statistically significant increase in systolic blood pressure and diastolic blood pressure [ 2 ].…”
Section: Introductionmentioning
confidence: 99%